A pilot study on assessment of knowledge and clinical reasoning in acute asthma management among healthcare provider in emergency department HUSM using k-cramed inventory - Mohamed, Saiful Azlan (2017)
Introduction: Acute asthma attack is a common presentation to emergency department. Thus, healthcare provider at emergency department need to have sufficient knowledge and acceptable level of clinical reasoning to manage such cases. Objective: This study aimed to determine the cut off score for level of knowledge and clinical reasoning in acute asthma management through standard setting. Then attempt to assess level of knowledge and clinical reasoning in acute asthma management among healthcare provider in Emergency Department Hospital Universiti Sains Malaysia. Methodology: This study was a cross-sectional study from January 2017 until March 2017 at Emergency Department (ED) Hospital Universiti Sains Malaysia (HUSM). All healthcare provider available at ED HUSM from January 2015 until March 2015 were included. Purposeful sampling was used, and a total of 178 participants were involved in this study. K-CRAMED inventory were used as the tool to assess knowledge and clinical reasoning. Descriptive statistics were expressed as frequency (percentage) or mean ± standard deviation for numerical variables. For association study, Independent- Sample T Test, Pearson Correlation test and One-Way ANOVA were used. Standard setting was implemented using Angoff Method and Modified Angoff Method involving five specialists from ED HUSM. Results: Participants for this study consists of 178 people. The participants consist of 68 (38.2%) staff nurses, 66 (37.1%) postgraduate students, 20 (11.2%) medical assistants, 15 (8.4%) house officers and 9 (5.1%) service medical officers. Most healthcare provider had working experience of between 5-10 year, which was 55.6%, 38.8% participant had experience less than five years, and another 5.6% had working experience of more than 10 years. Standard setting using Angoff Method and Modified Angoff Method and was done with five emergency physicians from ED HUSM. Cut off score for adequacy of knowledgewere highest in the postgraduate students group with 75.6%, while the lowest cut off score was for the medical assistant group and staff nurses group with 28.4%. For level of clinical reasoning, postgraduate students received the highest cut off score of 66.8%, while the lowest cut off score was 29.9% also shared by both medical assistants and staff nurses group. This study found that majority of postgraduate students had inadequate knowledge (78.8%) and inadequate clinical reasoning (90.9%). A proportion of service medical officers, house officers, medical assistants and staff nurses also having inadequate level of clinical reasoning with total of 55.6%, 13.3%, 25.0% and 39.7% respectively. Association study found that males had higher mean score than female in level of knowledge (p = 0.020). However, there was no significant difference in level of clinical reasoning with gender (p = 0.055). Increase in age had a moderate positive correlation with level of knowledge (p = 0.000) and level of clinical reasoning (p = 0.047). While work experience had no relationship with level of knowledge (p = 0.053) or level of clinical reasoning (p = 0.539). Conclusions: Majority of postgraduate students had inadequate level of knowledge and clinical reasoning. A proportion of other healthcare provider also having inadequate level of clinical reasoning. Intervention by the department is needed to fill in the knowledge gap and to achieve acceptable level of clinical reasoning.